Epidemiology of genital warts in the British population: implications for HPV vaccination programmes. (5th February 2019) - Sonnenberg, Pam; Tanton, Clare; Mesher, David; King, Eleanor; Beddows, Simon; Field, Nigel; Mercer, Catherine H; Soldan, Kate; Johnson, Anne M
Abstract : Objectives: To estimate the prevalence of, and describe risk factors for, genital warts (GWs) in the British population, following the introduction of the bivalent (human papillomavirus (HPV)-16/18) vaccination programme in girls, and prior to the switch to quadrivalent (HPV-6/11/16/18) vaccine (offering direct protection against GWs) and compare this with GW diagnoses in the prevaccination era. Methods: Natsal-3, a probability sample survey in Britain, conducted in 2010–2012, interviewed 9902 men and women aged 16–44. Natsal-2, conducted in 1999–2001, surveyed 11 161 men and women aged 16–44. Both surveys collected data on sexual behaviour and sexually transmitted infection diagnoses using computer-assisted interview methods. Results: In Natsal-3, 3.8% and 4.6% of sexually experienced men and women reported ever having a diagnosis of GWs, with 1.3% of men and 1.7% of woman reporting a GWs diagnosis in the past 5 years. GWs were strongly associated with increasing partner numbers and condomless sex. Diagnoses were more frequent in men who have sex with men (MSM) (11.6% ever, 3.3% past 5 years) and in women reporting sex with women (10.8% ever, 3.6% past 5 years). In the age group who were eligible for vaccination at the time of Natsal-3 (16–20 years), a similar proportion of same-aged women reported a history of GWs in Natsal-2 (1.9%, 1.1–3.4) and Natsal-3 (2.6%, 1.5–4.4). Conclusions: These data provide essential parameters for mathematical models that inform cost-effectiveness analyses of HPV vaccination programmes. There was no evidence of population protection against GWs conferred by the bivalent vaccine. Even with vaccination of adolescent boys, vaccination should be offered to MSM attending sexual health clinics.